2023
DOI: 10.1371/journal.pone.0292021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pre-existing coronary heart disease on the prognosis of COVID-19 patients: A systematic review and meta-analysis

Saikun Wang,
Ruiting Zhu,
Chengwei Zhang
et al.

Abstract: Although studies have shown severe Coronavirus disease 2019 (COVID-19) outcomes in patients with pre-existing coronary heart disease (CHD), the prognosis of COVID-19 patients with pre-existing CHD remains uncertain primarily due to the limited number of patients in existing studies. This study aimed to investigate the impacts of pre-existing CHD on the prognosis of COVID-19 patients. Five electronic databases were searched for eligible studies. This article focused on cohort and case-control studies involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 103 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that patients with pre-existing HF are at an elevated risk of excruciating ailment from COVID-19, with nearly one-third of such patients dying during hospitalization [43]. COVID-19 can exacerbate heart failure through several mechanisms, including inflammation, direct cardiac injury, and increased thrombotic activity [43][44][45][46]. A multicenter prospective study highlighted the role of NT-proBNP levels in predicting mortality in critically ill COVID-19 patients, with a 30-day mortality rate of 27.4% among the study participants [45].…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that patients with pre-existing HF are at an elevated risk of excruciating ailment from COVID-19, with nearly one-third of such patients dying during hospitalization [43]. COVID-19 can exacerbate heart failure through several mechanisms, including inflammation, direct cardiac injury, and increased thrombotic activity [43][44][45][46]. A multicenter prospective study highlighted the role of NT-proBNP levels in predicting mortality in critically ill COVID-19 patients, with a 30-day mortality rate of 27.4% among the study participants [45].…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
“…A multicenter prospective study highlighted the role of NT-proBNP levels in predicting mortality in critically ill COVID-19 patients, with a 30-day mortality rate of 27.4% among the study participants [45]. Patients with a high probability of HF experienced a notably elevated mortality and morbidity rate in comparison to those with a lower likelihood (40.8% vs. 16.5%, respectively) [44]. A study conducted by Saikun Wang highlights the substantial impact of pre-existing coronary heart disease (CHD) on COVID-19 outcomes [45].…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation